Nursing diagnoses in the post-anesthetic recovery room in patients undergoing orthopedic surgery (Research, Society and Development, 2020)
Cross-sectional, exploratory, descriptive study with a quantitative approach, carried out at a Regional Emergency and Trauma Hospital in the city of Campina Grande, Paraíba, Brazil. 127 patients were analyzed using a semi-structured form, including sociodemographic information, data from the surgical procedure and assessment of postoperative nursing diagnoses. For data analysis, the Statistical Package for the Social Sciences (SPSS), version 22.0, was used, considering the level of statistical significance of 5%. Descriptive analysis of the sample was performed, using mean and standard deviation to assess age and absolute and relative frequency for categorical variables. Of the 127 patients evaluated, the majority are male (70%), brown (50.4%), from surrounding cities (65.4%), with a predominance of incomplete elementary education (54.3%) as educational level. The main diagnoses identified in the POI were: impaired physical mobility (100%), impaired skin integrity (100%), risk of infection (100%), hypothermia (77%) and acute pain (100%). It is concluded that, in addition to managing the resources and the nursing team, it is up to the nurse to identify the complications and outline a care plan to implement with the orthopedic surgical patient, aiming to minimize its occurrence and to dynamize the Perioperative Nursing Care Systematization. It is suggested that further studies be carried out, since there is still no specific and validated instrument to meet the needs of perioperative nursing in an integral manner to the orthopedic surgical patient.